Famous business fusions : ideas that revolutionized industries - Meadows, CJ (High-Impact Business Innovation Series ,, 2021)
Where do startup founders and product developers get radical, high-value ideas? This book presents innovation behind-the-scenes stories from companies such as Apple, Airbnb, Coca-Cola, Google, P&G, Uber, and more. It reveals where the ideas came from and provides guidance on how you, too, can combine unlikely ideas to create new offerings and startup ventures by integrating industries, fields, technologies, and people. Famous Business Fusions discusses how an idea from one place, transported somewhere new, can lead to radically creative innovation. The book is replete with stories of lateral thinking or "fusion" that inspire you to think bigger, discover deeper insights, sense real opportunities and craft high-value fusion. This book is essential reading for those interested in new inventions, innovation and entrepreneurship; business leaders and consultants involved in innovation and new product or service development; and academics seeking material on business innovation and startups.